Effect of Progressive Muscle Relaxation on The Functional Status of The Elderly in The Integrated Services Unit of The Elderly Binjai - Eqlima Elfira; Nurbaiti Nurbaiti; Roxsana Devi Tumanggor (Universitas Respati Yogyakarta, 2020)
The elderly are very vulnerable to overcome musculoskeletal disorders such as joint pain and back pain. The estimated health status of the elderly can be changed in their Functional Status, which will affect Physical, psychological, and spiritual. This study discusses progressive muscle relaxation training in the Functional status of the elderly in the Binjai Elderly Integrated Services Unit. The research method was conducted by pre-experiment with the design of one group pretest-posttest. The number of samples consisted of categories from 60 years to 82 years, collected 33 people. The implementation method is done with progressive relaxation exercises for 30 minutes in a seated position with 15 hand and foot movements with 33 elderly people repeatedly. Data collection tools in this study use demographic data questionnaires and Barthel index. Data analysis using Pearson correlation coefficient, where the value of sig. (2-tailed) 0.085> 0.05 which means there is no significant effect between progressive muscle relaxation exercises with the functional status of the elderly. The progressive muscle relaxation exercises only experience changes in vital signs so that it is very effective in a sitting or standing position.